Nationalism and ethnosymbolism : history, culture and ethnicity in the formation of nations - Grosby, Steven Elliott, 1951-; Leoussi, Athena S., 1959- (Edinburgh University Press, 2007)
Ethnosymbolism offers a distinct and innovative approach to the study of nations and nationalism. It focuses on the role of ethnic myths, historical memories, symbols and traditions in the creation and maintenance of the collective identity of modern nations. This book explores the different aspects of the ethnosymbolic approach to the study of ethnicity, nationality and nationalism. Nationalism and Ethnosymbolism first introduces the main theoretical considerations that have arisen in nationalism studies in the past two decades. It then presents a collection of case studies covering music and.